Tinea folliculorum complicating tinea of the glabrous skin: an important yet neglected entity. (26th October 2017) - Sun, Pei-Lun; Lin, Yang-Chih; Wu, Yu-Hung; Kao, Pei-Han; Ju, Yu-Ming; Fan, Yun-Chen
Abstract: Dermatophytes are capable of infecting the skin and its appendages such as nails and hairs producing a variety of clinical conditions. Hair invasion by dermatophytes is a key feature of tinea capitis and tinea barbae but not of tinea of glabrous skin. In this project, we studied the clinico-mycological aspects of follicular involvement in patients with dermatophytosis of the glabrous skin. In total, 16 patients, eight males and eight females, were included in the study. All were adults except for one girl. The disease durations ranged from one month to more than ten years. Fourteen (78.5%) had multiple lesions, and most of them had undergone treatment with antifungals, antibiotics, or steroids. Dermoscopic examination showed infected hairs in the form of broken stubs, coily, curly, or as black dots on the surface of the lesions. Pathogens were either anthropophilic (seven cases of Trichophyton rubrum ) or zoophilic (six cases Microsporum canis, three cases of the T. mentagrophytes ). Patients responded well to oral griseofulvin or terbinafine, and topical antifungals. No antifungal resistance developed during the treatment course. Follicular involvement of glabrous skin is not as rare as previously thought and should be considered for systemic antifungal treatments.